2018
DOI: 10.1002/ana.25324
|View full text |Cite
|
Sign up to set email alerts
|

Association between carotid atheroma and cerebral cortex structure at age 73 years

Abstract: The findings suggest that carotid stenosis represents a marker of processes that accelerate aging of the cerebral cortex and cognition that is in part independent of measurable VRFs. Cortical thinning within the anterior and posterior circulation territories partially mediated the relationship between carotid atheroma and fluid intelligence. Ann Neurol 2018;84:576-587.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 37 publications
2
26
3
1
Order By: Relevance
“…This finding supports the assumption that the association between highgrade ICAOD and pathological alterations of cortical microstructure is directly mediated by a restriction of blood flow through the hemodynamically relevant large vessel pathology [16] and not by a widespread distal microvascular pathology. Thus, in contrast to what has been suggested earlier [7,54], ICAOD in this respect might not only be an indicator of generalized atherosclerosis affecting the cortical microstructure by direct involvement of the cerebral microcirculation. Although the macrovascular blood flow velocity as measured with Doppler/ultrasound is related to the regional blood flow of the more distal vasculature, it does not allow assessment of the hemodynamic situation on the tissue level in affected brain parenchyma.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…This finding supports the assumption that the association between highgrade ICAOD and pathological alterations of cortical microstructure is directly mediated by a restriction of blood flow through the hemodynamically relevant large vessel pathology [16] and not by a widespread distal microvascular pathology. Thus, in contrast to what has been suggested earlier [7,54], ICAOD in this respect might not only be an indicator of generalized atherosclerosis affecting the cortical microstructure by direct involvement of the cerebral microcirculation. Although the macrovascular blood flow velocity as measured with Doppler/ultrasound is related to the regional blood flow of the more distal vasculature, it does not allow assessment of the hemodynamic situation on the tissue level in affected brain parenchyma.…”
Section: Discussioncontrasting
confidence: 70%
“…Cortical thickness reflects the total content of neurons, the cellular composition and the cytoarchitectonic organization of a given cortical region [6] and therefore MRI-based estimation of cortical thickness is frequently used to investigate the integrity of the cerebral cortex on the microstructural level. A previous study demonstrated a significant relationship between unilateral carotid stenosis and widespread bilateral cortical thinning [7]. Other studies found an association between hemodynamic impairment and focal cortical K thinning [8][9][10][11], suggesting a direct detrimental effect of carotid occlusive disease on cortical microstructure; however, a recent study could not replicate this finding and found no influence of carotid stenosis on ipsilateral or contralateral cortical thickness in a multivariate analysis [12].…”
Section: Introductionmentioning
confidence: 95%
“…Karotis arter hastalıkları ile bilişsel bozuklukların ilişkisini araştıran pek çok çalışma vardır (16,17). Hem semptomatik hem de asemptomatik KAD'nın sağlıklı gönüllülerle karşılaştırıldığında kognitif testlerde kötüleşmeye yol açtığı birçok çalışma ile gösterilmiştir (9,(18)(19)(20)(21).…”
Section: Karotis Arter Darlığı Ve Kognitif Bozukluklarunclassified
“…5 Magnetic resonance imaging (MRI) can noninvasively evaluate brain structural changes and the pathophysiological mechanisms of ACS-related cognitive impairment. 6 Previous studies using structural MRI have identified cortical atrophy in patients with ACS. 6,7 Similarly, the atrophy of subcortical nuclei including the thalamus, caudate, putamen, pallidum, hippocampus, amygdala, and nucleus accumbens was also reported in patients with Alzheimer's disease dementia.…”
Section: Introductionmentioning
confidence: 99%
“…6 Previous studies using structural MRI have identified cortical atrophy in patients with ACS. 6,7 Similarly, the atrophy of subcortical nuclei including the thalamus, caudate, putamen, pallidum, hippocampus, amygdala, and nucleus accumbens was also reported in patients with Alzheimer's disease dementia. Moreover, in ACS patients, reduced cerebral blood flow 8 and decreased vascular reactivity 9 of the basal nuclei (caudate, pallidum and thalamus) were reported.…”
Section: Introductionmentioning
confidence: 99%